Recidivism After a Prison-Based Treatment Program: a Comparison Between a Treatment and Control Group Using Proportional Weighting Within Strata - Bosma, Anouk (Journal of developmental and life-course criminology, 2020)
Given the large potential of prison-based treatment programs, it is highly important to empirically evaluate such programs in various populations in various geographic regions. The current study focused on the Dutch Prevention of Recidivism Program, a prison-based treatment program that aims to lower re-offending rates among participants by administering an individualized treatment program that addresses the criminogenic needs of an individual offender. It aimed to assess the extent to which the program was effective in reducing the post-release re-offending rates of program participants. This was studied by analyzing official prison data, risk assessment data, and re-offending records of a population-based sample of males incarcerated in The Netherlands. Proportional weighting within strata was applied to minimize selection effects. Study results showed that prisoners who completed a standard treatment program (which only consisted of phased re-entry), re-offended less in the 24 months post-release, compared to offenders in the control condition. This treatment effect was, however, not found when comparing prisoners who had completed a standard program plus cognitive skill training or substance abuse treatment, to those who had not. It was consequently concluded that participation in the prison-based Prevention of Recidivism program had a positive effect on post-release re-offending, for offenders who had engaged in a standard program that did not include any behavioral treatment modules. Results were discussed in light of theoretical and empirical considerations.